PEDAGOGICAL SIGNIFICANCE OF ORGANIZING SPORT COMPETITIONS - Xudayberdiyeva Xuriyat Karimberdiyevna (Galaxy International Interdisciplinary Research Journal, 2024)
The article describes the pedagogical importance of organizing sports competitions in educational institutions and how they affect the general growth and well-being of students.